Economics of Using Drip Irrigation System Round The Year For Different Crop Sequences - Saini, A K; Singh, K G; Siag, Mukesh (Journal of Agricultural Engineering, 2006)
A drip irrigation system was evaluated for different crop sequences, which consist of vegetable crop sequence, vegetable and field crop sequence and only field crop sequence. Economic analysis of these crop sequences was performed for two different situations. (i) Under unlimited water supplies - out of three crop sequences, vegetable crop sequence of Cauliflower-Hybrid chilly gave maximum net return with drip irrigation method as compared to other crop sequences with drip and conventional irrigation method. The net return for this crop sequence with drip irrigation method was 1.49 times higher as compared to conventional irrigation method. (ii) Under Limited water supplies - Drip irrigation method gave substantially higher net returns for vegetable crop sequence, because water saved with drip irrigation method can be used to irrigate the additional area. The net return with drip was 3.6 times higher as compared to conventional irrigation method. Other crop sequences with drip irrigation method also gave nearly equivalent net return as compared to conventional method of irrigation.